Analysis of Difficulty Index, Discrimination Index and Distractor Efficiency of Multiple Choice Questions of Speech Sounds of English - Sharma, Lok Raj (International Research Journal of MMC, 2021)
The prime purpose of this research article is to analyze 20 multiple choice questions (MCQs) regarding the consonant and vowel sounds of English having asked to the Bachelor of Education (B. Ed) first year major English students in their achievement examination conducted at Makawanpur Multiple Campus, Hetauda, Nepal in 2020. The researcher employed 33% students from the group of high achievers from the top and 33% students from the group of low achievers from the bottom by including 18 students from the population of 27 students. Each item was analyzed for difficulty index (DIF I), discrimination index (DI), and distractor effectiveness (DE). 3 (15%) questions fell in the range of the difficulty index of (0.20 – 0.39). 14 (70%) questions fell in the range of the difficulty index of (0.40 – 0.59).  2 (10%) questions fell in the range of the difficulty index of (0.60 – 0.79).  1 (5%) Question fell in the range of the difficulty index of (0.80 – 0.89).  2 (10%) questions lay in the discrimination index of (0.20-0.29) and 18 (90%) questions lay in the discrimination index of    5 (25%) questions had one non-functional distractor, whereas 15 (75%) questions had zero nun-functional distractor. Out of 60 distractors, 5 (8.34%) distractors were non-functional and 55 (91.66%) distractors were functional. It was found that most of the multiple choice questions were reliable and valid.